Editorial Note - Editor (Interprofessional Journal of Health Sciences, 2025)
Scientific inquiry is a dynamic and ongoing process that depends heavily on collaboration and the transparent sharing of knowledge. While careful control of experimental conditions is essential for maintaining scientific rigor, equal importance should be placed on selecting effective and accessible channels for communicating research findings. In an increasingly interconnected global research landscape, it is no longer appropriate for scholarly work to remain confined to specific institutions or regions. To genuinely stimulate innovation, research outcomes must be shared broadly and equitably. This obligation is especially important for publicly funded research, as the knowledge generated should be accessible to the wider community rather than limited to a select audience. The Interprofessional Journal of Health Sciences (Interprof. J. Health Sci.) is deeply committed to promoting open access to scientific research. By publishing exclusively in English—the common language of the international scientific community—the journal enables newly generated knowledge to reach a broad global readership. In response to the rapid expansion of scientific output, the journal welcomes a wide variety of manuscript types, including original research articles, systematic and narrative reviews, case reports, short communications, and editorial correspondence. The journal’s central aim is to disseminate high-quality research across a wide range of disciplines, including health sciences, biomedical research, technological innovation, and socio-medical studies. Both current and forthcoming issues present diverse interdisciplinary and biologically focused contributions that offer valuable perspectives to inform, support, and enrich readers’ scholarly work. As an active participant in the global scientific community, Interprof. J. Health Sci. recognizes that scientific advancement is typically gradual, with major breakthroughs emerging from the steady accumulation of smaller discoveries. To advance this mission, the journal provides an inclusive and dependable platform for researchers from Thailand and around the world to share their work. Manuscript submission is managed through an efficient online system (https://li05.tci-thaijo.org/index.php/IJHS), designed to ensure ease of access and user-friendly navigation. The editorial team sincerely thanks all authors who contributed to the current volume, particularly those who submitted their manuscripts within tight timelines. We also extend our appreciation to the peer reviewers, whose expertise and constructive feedback are essential to maintaining the journal’s academic standards and editorial excellence. Finally, we welcome comments and suggestions from our readers as we continue to expand the scope, quality, and international influence of Interprof. J. Health Sci.